Determination of IgA- and IgM-rheumatoid factors in patients with rheumatoid arthritis with and without nephropathy. - Nakano, M (1996)
OBJECTIVE: To clarify the characteristics and pathogenesis of renal disorders in patients with rheumatoid arthritis (RA). METHODS: In this study, 143 patients with RA were included, from whom 43 with urinary abnormalities were biopsied. Serum rheumatoid factor (RF) concentrations of IgA and IgM isotypes were also measured in these patients by enzyme linked immunosorbent assay. RESULTS: Light microscopy of renal biopsy specimens showed minor glomerular abnormalities in six patients, mesangial proliferative glomerulonephritis (GN) in 21, membranous nephropathy in seven, renal amyloidosis in seven, and tubulointerstitial nephritis in two. Twelve patients with mesangial proliferative GN and one with minor glomerular abnormalities were found by immunofluorescence microscopy to have abnormalities consistent with IgA GN. Although the concentrations of IgA-RF in patients with IgA GN were slightly raised compared with those with glomerulopathy established by biopsy but not associated with IgA GN, the concentrations of IgA-RF were higher in patients with RA with vasculitis or interstitial pneumonia than those with RA complicated by IgA GN. CONCLUSIONS: Mesangial proliferative GN, including IgA GN, may be a frequent renal lesion in Japanese patients with RA. IgA-RF may play little pathogenetic part in the development of IgA GN in RA.